Boron-based bioactive glasses: Properties, processing, characterization and applications. Issue 12 (15th June 2023) - Aslam, Awais Ali; Akram, Javeria; Mehmood, Rana Adeel; Mubarak, Arifa; Khatoon, Amna; Akbar, Uzma; Ahmad, Sheikh Asrar; Atif, Muhammad
Abstract: The performance of many biological processes is thought to be affected by boron, and a deficiency is linked to delayed bone growth. Boron is therefore a bioactive element that is advantageous to both people and animals. Another well-known benefit of boron is that it promotes bone growth and wound healing. Glass structure, glass processing properties, biodegradability, biocompatibility, bioactivity, and cytotoxicity are all significantly impacted by the introduction of boron to bioactive glasses in a range of concentrations. According to research so far, boron based bioactive glasses (BBGs) frequently surpass silicate glasses in terms of bioactivity and potential for bone healing. Additionally, they could be employed as medication delivery systems for the treatment of infections and conditions like osteoporosis. By adding modifying ions, BBGs capacity to heal wounds or repair bone can be increased. Boron based bioactive glasses are typically synthesized via melt-quenching, although a more recent, more promising technique sol-gel processing is starting to attract interest. This review analyses the available literature to offer an in-depth overview of BBG properties, their real-world applications, challenges, and suggestions for future study. Graphical abstract: Image 1